193k views
0 votes
30 POINTS AVAILABLE

1.
Write the equation of a circle with the endpoints of the diameter at (-1, 6) and (5, -4). Watch the signs!

User Marekb
by
4.5k points

1 Answer

2 votes

Answer:


\large\boxed{(x-2)^2+(y-1)^2=34}

Explanation:

The equation of a circle in standard form:


(x-h)^2+(y-k)^2=r^2

(h, k) - center

r - radius

We have the endpoints of the diameter: (-1, 6) and (5, -4).

Midpoint of diameter is a center of a circle.

The formula of a midpoint:


\left((x_1+x_2)/(2);\ (y_1+y_2)/(2)\right)

Substitute:


h=(-1+5)/(2)=(4)/(2)=2\\\\k=(6+(-4))/(2)=(2)/(2)=1

The center is in (2, 1).

The radius length is equal to the distance between the center of the circle and the endpoint of the diameter.

The formula of a distance between two points:


d=√((x_2-x_1)^2+(y_2-y_1)^2)

Substitute the coordinates of the points (2, 1) and (5, -4):


r=√((5-2)^2+(-4-1)^2)=√(3^2+(-5)^2)=√(9+25)=√(34)

Finally we have:


(x-2)^2+(y-1)^2=(√(34))^2

User Jbarnett
by
4.9k points